Solid electrolyte ceramics and solid batteries

By using garnet-type solid electrolyte ceramics with specific chemical composition in solid batteries, the problem of increasing electron conductivity caused by Li-Bi-O-type impurities is solved, and higher ion conductivity and lower electron conductivity are achieved, avoiding short circuits and leakage currents of solid batteries.

CN116420243BActive Publication Date: 2025-02-25MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180076899.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-17
Filing Date
2021-11-17
Publication Date
2025-02-25
Estimated Expiration
2041-11-17

AI Technical Summary

Technical Problem

In solid batteries using garnet-type solid electrolyte ceramics containing Bi, Li-Bi-O-type impurities are easily generated from grain boundaries, resulting in an increase in electron conductivity and short circuit and leakage current problems.

Method used

A solid electrolyte ceramic with a garnet-type crystal structure is adopted. Its chemical composition is composed of Li, La, O and transition metal elements Co, Ni, Mn, and Fe. The formation of Li-Bi-O-type impurities is inhibited through specific chemical composition ratios and heat treatment conditions.

Benefits of technology

The ion conductivity in solid batteries is improved, while the increase in electron conductivity is effectively suppressed and the problems of short circuit and leakage current are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004228630930000291
    Figure BDA0004228630930000291
  • Figure BDA0004228630930000301
    Figure BDA0004228630930000301
Patent Text Reader

Abstract

The present invention provides a solid electrolyte ceramic having excellent ion conductivity and capable of more fully suppressing the increase in electronic conductivity caused by the operation of a solid battery. The present invention relates to a solid electrolyte ceramic having a garnet-type crystal structure, containing at least Li (lithium), La (lanthanum) and O (oxygen), and containing one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese) and Fe (iron), wherein the content X (mol %) of one or more elements D selected from the group consisting of transition elements capable of forming hexacoordinates with oxygen and typical elements belonging to Groups 12 to 15 and the total content Y (mol %) of the transition metal elements satisfy a specific relationship.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte ceramic and a solid battery comprising the solid electrolyte ceramic. Background Art

[0002] In recent years, the demand for batteries as power sources for portable electronic devices such as mobile phones and portable personal computers has increased significantly. As batteries for such applications, sintered solid secondary batteries (so-called "solid batteries") using solid electrolytes as electrolytes and other components also consisting of solids are being developed.

[0003] The solid battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer stacked between the positive electrode layer and the negative electrode layer. In particular, the solid electrolyte layer includes a solid electrolyte ceramic, which is responsible for the conduction of ions between the positive electrode layer and the negative electrode layer. The solid electrolyte ceramic requires higher ion conductivity and lower electronic conductivity. As such a solid electrolyte ceramic, from the viewpoint of higher ion conductivity, an attempt has been made to use a ceramic sintered by a garnet-type solid electrolyte substituted with Bi (for example, Patent Document 1 and Non-Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-050071

[0007] Non-patent literature

[0008] Non-patent document 1: Gao et al., Solid State Ionics, 181 (2010) 1415-1419 Summary of the invention

[0009] The inventors of the present invention have found that the following problems occur in solid batteries using the above-mentioned conventional solid electrolyte ceramics. Specifically, in conventional solid batteries using garnet-type solid electrolyte ceramics containing Bi, impurities such as Li-Bi-O compounds are easily generated at the grain boundaries, and the Li-Bi-O compounds are reduced when the solid battery is operating (i.e., during charging and discharging), and the electronic conductivity increases. If the electronic conductivity increases, the solid battery short-circuits and / or causes an increase in leakage current.

[0010] The inventors of the present invention have also found that, from the viewpoint of suppressing the formation of Li-Bi-O compounds, it is effective to contain transition metal elements such as Co, but it has also been found that the following new problems arise. Specifically, if a relatively large amount of transition metal elements such as Co (the first transition metal element described later) are contained, impurities containing transition metals such as Li-La-Co-O compounds different from Li-Bi-O compounds are generated, and these impurities also increase the electronic conductivity when the solid battery is operating.

[0011] An object of the present invention is to provide a solid electrolyte ceramic having excellent ion conductivity and capable of more fully suppressing an increase in electron conductivity caused by the operation of a solid battery.

[0012] Another object of the present invention is to provide a solid electrolyte ceramic having excellent ion conductivity even when containing a relatively large amount of a transition metal element (a first transition metal element described later) while more fully suppressing the increase in electronic conductivity caused by the operation of a solid battery.

[0013] The present invention relates to a solid electrolyte ceramic having a garnet-type crystal structure, containing at least Li (lithium), La (lanthanum) and O (oxygen), and containing one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese) and Fe (iron),

[0014] The solid electrolyte ceramic has the following general formula (I):

[0015] [Chemical formula 1]

[0016] A α B β D γ O ω (I)

[0017] (In formula (I), A is one or more elements selected from the group consisting of Li (lithium), Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium), and contains at least Li (lithium);

[0018] B is one or more elements selected from the group consisting of La (lanthanum), Ca (calcium), Sr (strontium), Ba (barium) and lanthanide elements, and contains at least La (lanthanum);

[0019] D is one or more elements selected from the group consisting of transition elements capable of forming hexacoordination with oxygen and typical elements belonging to Groups 12 to 15;

[0020] α satisfies 5.0≤α≤8.0;

[0021] β satisfies 2.5≤β≤3.5;

[0022] γ satisfies 1.5≤γ≤2.5;

[0023] ω satisfies 11≤ω≤13)

[0024] The chemical composition of

[0025] When the content of D is X (mol%) when the content of B is 100 mol%, and the total content of the transition metal elements is Y (mol%), any one of the following relationship equations (1) to (3) is satisfied:

[0026] (1) 0.01≤Y≤4.00 in the range of 12.0≤X<20.0;

[0027] (2) 0.01≤Y≤6.00 in the range of 20.0≤X<33.0;

[0028] (3) 0.01≤Y≤8.00 in the range of 33.0≤X≤65.5.

[0029] The solid electrolyte ceramic of the present invention has excellent ion conductivity and can more fully suppress the increase in electronic conductivity caused by the operation of the solid battery. DETAILED DESCRIPTION

[0030] [Solid Electrolyte Ceramics]

[0031] The solid electrolyte ceramic of the present invention is composed of a sintered body formed by sintering solid electrolyte particles. The solid electrolyte ceramic of the present invention is a solid electrolyte ceramic containing at least Li (lithium), La (lanthanum) and O (oxygen) and having a garnet-type crystal structure, and also contains one or more transition metal elements selected from the group consisting of Co (cobalt), Ni (nickel), Mn (manganese) and Fe (iron) (hereinafter sometimes referred to as "the first transition metal element"). In addition, the solid electrolyte ceramic of the present invention is a ceramic composed of a solid electrolyte having a garnet-type crystal structure, and may also contain other composite oxides or single oxides within the scope of not impairing the effect of the present invention. In addition, from the viewpoint of more excellent ion conductivity and more fully suppressing the increase in electronic conductivity during operation, it is preferred to contain Bi (bismuth). In addition, the sintered particles contained in at least the solid electrolyte ceramic as the main component of the present invention have a garnet-type crystal structure.

[0032] The solid electrolyte ceramic of the present invention preferably has a chemical composition represented by the following general formula (I), and further contains a first transition metal element.

[0033] [Chemical formula 2]

[0034] Aα B β D γ O ω (I)

[0035] In formula (I), A is one or more elements selected from the group consisting of Li (lithium), Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium), and contains at least Li.

[0036] B is one or more elements selected from the group consisting of La (lanthanum), Ca (calcium), Sr (strontium), Ba (barium) and lanthanoid elements, and contains at least La. Examples of lanthanoid elements include Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium).

[0037] D represents one or more elements selected from the group consisting of transition elements capable of forming hexacoordinates with oxygen and typical elements belonging to Groups 12 to 15. As transition elements capable of forming hexacoordinates with oxygen, for example, Sc (scandium), Zr (zirconium), Ti (titanium), Ta (tantalum), Nb (niobium), Hf (hafnium), Mo (molybdenum), W (tungsten) and Te (tellurium) can be cited. As typical elements belonging to Groups 12 to 15, for example, In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony) and Bi (bismuth) can be cited. From the viewpoint of better ion conductivity and more fully suppressing the increase in electronic conductivity during operation, D preferably contains at least Bi and / or Ta, more preferably contains Bi and Ta, and further preferably contains Bi, Ta and Zr.

[0038] In formula (I), α, β, γ, and ω satisfy 5.0≤α≤8.0, 2.5≤β≤3.5, 1.5≤γ≤2.5, and 11≤ω≤13, respectively.

[0039] From the viewpoint of achieving better ion conductivity and more fully suppressing an increase in electronic conductivity during operation, α preferably satisfies 5.0≤α≤7.0, more preferably satisfies 5.00≤α≤6.35, further preferably satisfies 5.80≤α≤6.35, and particularly preferably satisfies 6.15≤α≤6.35.

[0040] From the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electronic conductivity during operation, β preferably satisfies 2.5≤β≤3.3, more preferably satisfies 2.5≤β≤3.1, and still more preferably satisfies 2.8≤β≤3.0.

[0041] From the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electronic conductivity during operation, γ preferably satisfies 1.8≤γ≤2.5, more preferably satisfies 1.8≤γ≤2.3, and still more preferably satisfies 1.9≤γ≤2.3.

[0042] From the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electron conductivity during operation, ω preferably satisfies 11≤ω≤12.5, and more preferably satisfies 11.5≤ω≤12.5.

[0043] In the present invention, the solid electrolyte ceramic has a chemical composition represented by the general formula (I), and when the content of D is X (mol%) when the content of B is 100 mol%, and the total content of the first transition metal element is Y (mol%), any one of the above-mentioned relationship equations (1) to (3) is satisfied, thereby, even if the first transition metal element is contained in a relatively large amount, it has excellent ion conductivity and more fully suppresses the increase in electronic conductivity. In such a solid electrolyte ceramic, if the total content of D is too small, the increase in electronic conductivity cannot be fully suppressed. When the total content of D is too much, the ion conductivity decreases. In the present invention, it is preferred that D also contains one or more transition metal elements selected from the group consisting of Ta (tantalum) and Nb (niobium) (hereinafter sometimes referred to as "second transition metal element").

[0044] In the present invention, the contents of D and the first transition metal element in the solid electrolyte ceramic are specifically as follows. That is, when the total content of D when the content of B in the general formula (I) representing the chemical composition of the solid electrolyte ceramic of the present invention is 100 mol % is set to X (mol %), and the total content of the first transition metal element is set to Y (mol %), the solid electrolyte ceramic of the present invention satisfies any one of the following relationship equations (1) to (3):

[0045] (1) in the range of 12.0≤X<20.0 (particularly 13.0≤X<20.0 or 13.0≤X≤18.0), 0.01≤Y≤4.00 (a composite range of 0.01≤Y<1.40 and 1.40≤Y≤4.00) (from the viewpoint of more excellent ion conductivity and more sufficient suppression of increase in electronic conductivity during operation, preferably 0.01≤Y≤3.50 (a composite range of 0.01≤Y<1.50 and 1.50≤Y≤3.50), more preferably 0.02≤Y≤3.40 (a composite range of 0.02≤Y<1.60 and 1.60≤Y≤3.40));

[0046] (2) 0.01≤Y≤6.00 (a composite range of 0.01≤Y<1.40 and 1.40≤Y≤6.00) in the range of 20.0≤X<33.0 (particularly 20.0≤X≤30) (from the viewpoint of more excellent ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01≤Y≤5.50 (a composite range of 0.01≤Y<1.50 and 1.50≤Y≤5.50), more preferably 0.02≤Y≤5.20 (a composite range of 0.02≤Y<1.60 and 1.60≤Y≤5.20));

[0047] (3) In the range of 33.0≤X≤65.5 (particularly 33.0≤X≤65.0), 0.01≤Y≤8.00 (a composite range of 0.01≤Y<1.40 and 1.40≤Y≤8.00) (from the viewpoint of more excellent ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, preferably 0.01≤Y≤7.50 (a composite range of 0.01≤Y<1.50 and 1.50≤Y≤7.50), more preferably 0.02≤Y≤7.00 (a composite range of 0.02≤Y<1.60 and 1.60≤Y≤7.00)). In addition, it is preferred that the second transition metal element of the present invention is contained in D, and it is more preferred that the content of the second transition metal element satisfies the range of X.

[0048] In each of the relational expressions (1) to (3), if the total content Y of the first transition metal elements exceeds a predetermined value by too much, the increase in electron conductivity cannot be sufficiently suppressed.

[0049] From the viewpoint of more excellent ion conductivity and more fully suppressing the increase in electronic conductivity during operation, the total content X of D specified in the present invention is preferably the total content of Ta and / or Nb and Bi, more preferably the total content of Ta and / or Nb, Bi and Zr, further preferably the content of Ta and Bi, and particularly preferably the content of Ta.

[0050] The total content X of D and the total content Y of the first transition metal element can be expressed as a ratio (mol%) when the content of B is 100 mol%, or can be expressed as a ratio (mol%) when the number of 8 coordination sites in the garnet type crystal structure is 100 mol%. For example, in the case of the chemical composition of the general formula (II) described later, the ratio can be expressed as: 1 The value of the ratio (mol%) when the total number is 100 mol%. In other specific examples, the 8-coordinated site in the garnet-type crystal structure is, for example, Li5La3Nb2O having a garnet-type crystal structure. 12The La site in (ICDD Card No. 00-045-0109) is also a garnet-type crystal structure Li7La3Zr2O 12 The site occupied by La in (ICDD Card No. 01-078-6708).

[0051] The content of D and the content of the first transition metal element can be measured by performing inductively coupled plasma (ICP: Inductively Coupled Plasma) emission spectrometry analysis (ICP analysis) of the solid electrolyte ceramic to obtain the average chemical composition of the material. Specifically, the average chemical composition can be obtained based on the ICP analysis, and the content of the elements contained in D, such as Ta and Nb, and the content of Co, Mn, Ni and Fe in the general formula (I) (for example, La and B in the general formula (II) described later) can be obtained based on the average chemical composition. 1 The ratio when the total number of (mol%) is 100 mol%. It should be noted that it can also be measured and calculated using an X-ray photoelectron spectrometer (XPS: X-ray Photoelectron Spectroscopy).

[0052] The Bi (bismuth) content is usually 25 mol% or less when the D content is 100 mol%. From the viewpoint of more excellent ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it is preferably more than 0 mol% and less than 25 mol%, more preferably more than 0 mol% and less than 15 mol%, further preferably more than 0 mol% and less than 12 mol%, particularly preferably more than 1 mol% and less than 12 mol%, and most preferably more than 5 mol% and less than 12 mol%.

[0053] The Bi content can also be measured by performing inductively coupled plasma (ICP: Inductively Coupled Plasma) emission spectrometry analysis (ICP analysis) of the solid electrolyte ceramic to obtain the average chemical composition of the material. Specifically, the average chemical composition can be obtained based on the ICP analysis, and the Bi content can be obtained based on the average chemical composition. 1 The ratio when the total number of (mol%) is 100 mol%. It should be noted that it can also be measured and calculated using an X-ray photoelectron spectroscopy analyzer (XPS: X-ray Photoelectron Spectroscopy).

[0054] From the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electronic conductivity during operation, the solid electrolyte ceramic of the present invention preferably satisfies the above-mentioned relational expression (1) or (2), and more preferably satisfies the above-mentioned relational expression (1).

[0055] The existence mode (or containing mode) of the first transition metal element in the solid electrolyte ceramic of the present invention is not particularly limited, and it may exist in the crystal lattice or outside the crystal lattice. For example, the first transition metal element may exist in the body, in the grain boundary, or in both in the solid electrolyte ceramic. As an example of the first transition metal element existing in the body, it means that in the solid electrolyte ceramic of the present invention, the first transition metal element exists in the metal site (lattice site) constituting the garnet-type crystal structure. The metal site may be any metal site, for example, it may be a Li site, a La site, a Bi site, or two or more of them. The solid electrolyte ceramic of the present invention is composed of a plurality of sintered particles, and the first transition metal element may also exist at the interface between two or more sintered particles.

[0056] In the case where the solid electrolyte ceramic of the present invention contains Bi, the existence mode (or containing mode) of Bi (bismuth) in the solid electrolyte ceramic of the present invention is not particularly limited. For example, the Bi (bismuth) may exist in the bulk, in the grain boundary, or in both in the solid electrolyte ceramic. From the viewpoint of insulation, it is preferred that Bi exists in the bulk. As an example of Bi existing in the bulk, in the solid electrolyte ceramic of the present invention, the Bi may also exist in the metal site (lattice site) constituting the garnet-type crystal structure.

[0057] In the present invention, the first transition metal and / or Bi (bismuth) may also be contained in a ceramic having a garnet-type crystal structure. In addition, the first transition metal and / or Bi (bismuth) may also exist as a composite oxide and / or a single oxide containing the first transition metal and / or Bi (bismuth) and / or an element constituting the garnet-type solid electrolyte of the present invention. It should be noted that the oxide may also be present in the interface between crystal particles of the ceramic having a garnet-type crystal structure as the main component of the present invention.

[0058] Li (lithium) and La (lanthanum) in the solid electrolyte ceramic of the present invention may generally exist in the bulk, and specifically, as an example, in the solid electrolyte ceramic of the present invention, they may also exist in the Li site and La site which are metal sites (lattice sites) constituting the garnet type crystal structure. In this case, Li (lithium) and La (lanthanum) may exist in the grain boundaries independently or as a composite oxide.

[0059] From the viewpoint of more fully suppressing an increase in electronic conductivity during operation, the first transition metal element contained in the solid electrolyte ceramic of the present invention is preferably selected from the group consisting of Co, Ni and Mn, more preferably selected from the group consisting of Co and Mn, and further preferably contains Co.

[0060] The element contained in D and the second transition metal element in the solid electrolyte ceramic of the present invention are usually present in the bulk, and more specifically, in the metal site (particularly the 6-coordinate site) constituting the garnet-type crystal structure.

[0061] From the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electronic conductivity during operation, the element contained in D and the second transition metal element contained in the solid electrolyte ceramic of the present invention preferably contain Ta.

[0062] In the present invention, the solid electrolyte ceramic having a garnet-type crystal structure means that the solid electrolyte ceramic may have not only a "garnet-type crystal structure" but also a "quasi-garnet-type crystal structure". In detail, the solid electrolyte ceramic of the present invention has a crystal structure that can be identified as a garnet-type or quasi-garnet-type crystal structure by a person skilled in the art in the field of solid batteries in X-ray diffraction. In more detail, the solid electrolyte ceramic of the present invention may show one or more main peaks corresponding to the Miller index inherent to the so-called garnet-type crystal structure (diffraction pattern: ICDD Card No. 422259) at a specified incident angle in X-ray diffraction, or may also be a quasi-garnet-type crystal structure, showing one or more main peaks with different incident angles (i.e., peak positions or diffraction angles) and intensity ratios (i.e., peak intensities or diffraction intensity ratios) from one or more main peaks corresponding to the Miller index inherent to the so-called garnet-type crystal structure due to composition differences. As a representative diffraction pattern similar to the garnet type crystal structure, for example, ICDD Card No. 00-045-0109 can be cited.

[0063] As a specific embodiment, the solid electrolyte ceramic of the present invention can generally be represented by the general formula (II). In detail, the solid electrolyte ceramic has a chemical composition represented by the general formula (II). It should be noted that at this time, the solid electrolyte ceramic of the present invention has a chemical composition represented by the general formula (II) and also contains a first transition metal element as described above.

[0064] [Chemical formula 3]

[0065] (Li p A 1 y )(La 3-z B 1z )(D 1 y-x1-x2 M x1 Bi x2 ) 12-δ (II)

[0066] In formula (II), A 1 Refers to the metal element occupying the Li site in the garnet crystal structure. 1 It is an element corresponding to A in the general formula (I), and may be one or more elements selected from the group consisting of elements other than Li among the same elements as the elements exemplified as A. A 1 Generally, it is one or more elements selected from the group consisting of Ga (gallium), Al (aluminum), Mg (magnesium), Zn (zinc) and Sc (scandium). From the viewpoint of better ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, A 1 Preferably, it is one or more elements selected from the group consisting of Ga (gallium) and Al (aluminum), and more preferably, it is both Ga and Al.

[0067] In formula (II), B 1 Refers to the metal element occupying the La site in the garnet crystal structure. 1 It is an element corresponding to B in the general formula (I), and may be one or more elements selected from the group consisting of elements other than La among the same elements as those exemplified as B. B 1 Typically, it is one or more elements selected from the group consisting of Ca (calcium), Sr (strontium), Ba (barium) and lanthanoid elements.

[0068] In formula (II), D 1 Refers to the 6-coordination site in the garnet crystal structure (garnet crystal structure Li7La3Zr2O 12 (ICDD Card No. 01-078-6708)) is a metal element at the site occupied by Zr. 1 It is an element corresponding to D in the general formula (I), and may be one or more elements selected from the group consisting of Bi among the same elements as the elements exemplified as D and elements other than M described later. D 1 Generally, it is one or more elements selected from the group consisting of Zr (zirconium), Hf (hafnium), Mo (molybdenum), W (tungsten) and Te (tellurium). From the viewpoint of better ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it is preferred to contain Zr (zirconium).

[0069] M is the second transition metal element.

[0070] In formula (II), x1 is equivalent to 0.03×X relative to the above X, and usually satisfies 0.36≤x1≤1.965, and particularly satisfies 0.39≤x1≤1.95. From the viewpoint of more excellent ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it is preferred to satisfy the range converted from the range of X in the above relationship (1) and (2), and more preferably to satisfy the range converted from the range of X in the above relationship (1). The range converted from the range of X in the above relationship refers to the range of x1 calculated by multiplying the range of X by 0.03. For example, the range converted from 12.0≤X<20.0 in the relationship (1) is 0.36≤x1<0.60.

[0071] x2 satisfies 0<x2≤1.00. From the viewpoint of better ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, it preferably satisfies 0.01≤x2≤0.70, more preferably satisfies 0.02≤x2≤0.40, further preferably satisfies 0.10≤x2≤0.40, particularly preferably satisfies 0.20≤x2≤0.35, and most preferably satisfies 0.25≤x2≤0.35.

[0072] x1+x2 generally satisfies 0.50≤x1+x2≤2.00. From the viewpoint of better ion conductivity and more sufficient suppression of the increase in electronic conductivity during operation, x1+x2 preferably satisfies 0.50≤x1+x2≤1.90, more preferably satisfies 0.50≤x1+x2≤1.50, further preferably satisfies 0.50≤x1+x2≤1.20, particularly preferably satisfies 0.50≤x1+x2≤1.00, and most preferably satisfies 0.60≤x1+x2≤0.85.

[0073] y satisfies 0≤y≤0.50, preferably satisfies 0≤y≤0.40, more preferably satisfies 0≤y≤0.30, further preferably satisfies 0≤y≤0.20, and particularly preferably is 0, from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation.

[0074] z satisfies 0≤z≤2.00, preferably satisfies 0≤z≤1.00, more preferably satisfies 0≤z≤0.50, and even more preferably is 0, from the viewpoint of more excellent ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation.

[0075] γ satisfies 1.5≤γ≤2.5, and preferably satisfies 1.8≤γ≤2.5, more preferably satisfies 1.8≤γ≤2.3, and further preferably satisfies 1.9≤γ≤2.3, from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation.

[0076] In formula (II), p generally satisfies 5.00≤p≤6.35, and preferably satisfies 5.80≤p≤6.35, and more preferably satisfies 6.15≤p≤6.35, from the viewpoint of achieving more excellent ion conductivity and more adequate suppression of an increase in electronic conductivity during operation.

[0077] a is A 1 As the average price of A 1 For example, when it is considered that the number of elements X with a valence of a+ is n1, the number of elements Y with a valence of b+ is n2, and the number of elements Z with a valence of c+ is n3, A 1 The average valence is a value represented by (n1×a+n2×b+n3×c) / (n1+n2+n3).

[0078] b is B 1 As the average price of B 1 For example, if the number of X with a valence of a+ is n1, the number of Y with a valence of b+ is n2, and the number of Z with a valence of c+ is n3, then B 1 The average price is the same as above A 1 The average price of the same value.

[0079] c is D 1 As the average price of D 1 For example, when it is considered that the number of the element X with a valence of a+ is n1, the number of the element Y with a valence of b+ is n2, and the number of the element Z with a valence of c+ is n3, D 1 The average price is the same as the above A 1 The average price of the same value.

[0080] δ represents the amount of oxygen deficiency, and may be 0. δ may generally satisfy 0≤δ<1. The amount of oxygen deficiency δ is difficult to quantitatively analyze even with the latest equipment, and therefore may be considered to be 0.

[0081] It should be noted that the molar ratio of each element in the chemical composition of the solid electrolyte ceramic of the present invention is not necessarily consistent with the molar ratio of each element in formula (II), and there is a tendency to deviate therefrom depending on the analysis method. However, as long as the composition deviation is not so great as to cause a change in the characteristics, the effect of the present invention can be achieved.

[0082] In the present invention, the chemical composition of the solid electrolyte ceramic can be the composition of the entire ceramic material obtained using ICP (inductively coupled plasma method). In addition, the chemical composition can be measured and calculated using XPS analysis, or can be obtained using TEM-EDX (energy dispersive X-ray spectroscopy) and / or WDX (wavelength dispersive X-ray spectroscopy). In addition, the chemical composition can also be obtained by performing quantitative analysis (composition analysis) on any 100 points of each of any 100 sintered particles and calculating their average value.

[0083] The content of the first transition metal element (i.e., Co, Ni, Mn, Fe) in the solid electrolyte ceramic of the present invention [for example, the content of B in the general formula (I) (or the content of La and B in the general formula (II)] 1 The molar ratio when the total number of (the total number of) is set to 100 mol% can be calculated by the following method. In the present invention, the chemical composition of the solid electrolyte ceramic can be obtained by performing ICP analysis (inductively coupled plasma method), LA-ICP-MS (laser ablation ICP mass spectrometry) analysis, etc. In addition, XPS analysis can be used for measurement and calculation, and TEM-EDX (energy dispersive X-ray spectroscopy) and WDX (wavelength dispersive X-ray spectroscopy) can also be used. In addition, the chemical composition can also be obtained by performing quantitative analysis (composition analysis) of any 100 points of each of any 100 sintered particles and calculating their average value.

[0084] For example, EDX or WDX analysis is to measure the cross section of a solid battery. The cross section of a solid battery refers to a cross section parallel to the stacking direction of the positive electrode layer, the solid electrolyte layer, and the negative electrode layer. The cross section of a solid battery can be exposed by grinding after the solid battery is embedded in a resin. There is no particular limitation on the method of cross-section grinding. After cutting with a cutting machine, grinding can be performed using grinding paper, chemical mechanical grinding, ion milling, etc. to expose the solid electrolyte layer. By quantitatively analyzing the exposed cross section (solid electrolyte layer) using EDX or WDX (wavelength dispersion type fluorescent X-ray analyzer), the molar ratio of Co, Ni, Mn, and Fe relative to B can be calculated.

[0085] In addition, for example, in TEM-EELS measurement, after the electrode layer or solid electrolyte layer of the solid battery is peeled off using FIB (focused ion beam), TEM-EELS (transmission microscope-electron energy loss spectroscopy: Electron Energy-Loss Spectroscopy) measurement of the solid electrolyte part is performed. Thus, the elements contained in B in the general formula (I) and Co, Ni, Mn, and Fe are detected, and the molar ratio of the content of Co, Ni, Mn, and Fe relative to B can be calculated.

[0086] Specific examples of the chemical composition of the solid electrolyte ceramic of the present invention include the following chemical compositions: In the chemical compositions shown below, the transition metal element after the hyphen (-) indicates that it may exist in the bulk and / or in the grain boundaries as described above.

[0087] Li 6.3 Ln3Z 1.28 Ta 0.42 Bi 0.3 O 12 -Co 0.05

[0088] Li 6.3 Ln3Z 1.28 Ta 0.42 Bi 0.3 O 12 -Co 0.1

[0089] Li 6.2 Ln3Z 1.2 Ta 0.5 Bi 0.3 O 12 -Co 0.05

[0090] Li 6.2 Ln3Z 1.2 Ta 0.5 Bi 0.3 O 12 -Co 0.1

[0091] Li 6.1 Ln3Z 1.1 Ta 0.6 Bi 0.3 O 12 -Co 0.05

[0092] Li 6.1 Ln3Z 1.1 Ta 0.6 Bi 0.3 O 12 -Co 0.1

[0093] Li 6.1 Ln3Z 1.1 Ta 0.6 Bi 0.3 O 12 -Co 0.15

[0094] Li 5.9 Ln3Z0.9 Head 0.8 Bi 0.3 O 12 -Even though 0.05

[0095] Crush 5.9 The3Zr 0.9 Head 0.8 Bi 0.3 O 12 -Even though 0.1

[0096] Crush 5.9 The3Zr 0.9 Head 0.8 Bi 0.3 O 12 -Even though 0.15

[0097] Crush 5.7 The3Zr 0.7 Ta1Bi 0.3 O 12 -Even though 0.05

[0098] Crush 5.7 The3Zr 0.7 Ta1Bi 0.3 O 12 -Even though 0.1

[0099] Crush 5.7 The3Zr 0.7 Ta1Bi 0.3 O 12 -Even though 0.15

[0100] Crush 5.7 The3Zr 0.7 Ta1Bi 0.3 O 12 -Even though 0.2

[0101] Crush 5.2 The3Zr 0.2 Head 1.5 Bi 0.3 O 12 -Even though 0.05

[0102] Crush 5.2 The3Zr 0.2 Head 1.5 Bi 0.3 O 12 -Even though 0.1

[0103] Li 5.2 Ln3Z 0.2 Ta 1.5 Bi 0.3 O 12 -Co 0.15

[0104] Li 5.2 Ln3Z 0.2 Ta 1.5 Bi 0.3 O 12 -Co 0.2

[0105] Li5La3 1.95 Bi 0.05 O 12 -Co 0.05

[0106] Li5La3 1.95 Bi 0.05 O 12 -Co 0.1

[0107] Li5La3 1.95 Bi 0.05 O 12 -Co 0.15

[0108] Li5La3 1.95 Bi 0.05 O 12 -Co 0.2

[0109] The specific example of the chemical composition described above contains Co as a transition element, and may contain Ni, Mn or Fe instead of Co.

[0110] [Method for producing solid electrolyte ceramics]

[0111] The solid electrolyte ceramic of the present invention can be obtained by mixing a compound containing a specified metal element (i.e., a starting material) with water, drying it, and then heat-treating it in O2. The compound containing the specified metal element is usually a mixture of compounds containing a metal element selected from the group consisting of Li (lithium), La (lanthanum), Bi (bismuth), a first transition metal element, and a second transition metal element. As the compound containing the specified metal element (i.e., a starting material), for example, lithium hydroxide monohydrate LiOH·H2O, lanthanum hydroxide La(OH)3, zirconium oxide ZrO2, tantalum oxide Ta2O5, bismuth oxide Bi2O3, cobalt oxide Co3O4, alkaline nickel carbonate hydrate NiCO3·2Ni(OH)2·4H2O, manganese carbonate MnCO3, iron oxide Fe2O3, lithium nitrate LiNO3, lanthanum nitrate hexahydrate La(NO3)3·6H2O, bismuth nitrate pentahydrate Bi(NO3)3·5H2O, cobalt nitrate, etc. can be listed. The mixing ratio of the compound containing the prescribed metal element is sufficient as long as the solid electrolyte ceramic of the present invention has a prescribed chemical composition after heat treatment. The heat treatment temperature is usually 500° C. to 1200° C., preferably 600° C. to 1000° C. The heat treatment time is usually 10 minutes to 1440 minutes, particularly 60 minutes to 600 minutes.

[0112] The solid electrolyte ceramic of the present invention may contain a sintering aid. As the sintering aid, any sintering aid known in the field of solid batteries can be used. Such a sintering aid preferably contains at least Li (lithium), B (boron) and O (oxygen), and the molar ratio of Li to B (Li / B) is 2.0 or more. Specific examples of such a sintering aid include Li3BO3, (Li 2.7 Al 0.3 )BO3、Li 2.8 (B 0.8 C 0.2 )O3, LiBO2.

[0113] The content of the sintering aid is usually preferably 0% to 10% by volume, and particularly preferably 0% to 5% by volume, relative to the garnet-type solid electrolyte.

[0114] [Solid-state battery]

[0115] The term "solid battery" as used in this specification refers in a broad sense to a battery whose constituent elements (especially the electrolyte layer) are composed of solids, and in a narrow sense to an "all-solid battery" whose constituent elements (especially all constituent elements) are composed of solids. The term "solid battery" as used in this specification includes so-called "secondary batteries" that can be repeatedly charged and discharged, and "primary batteries" that can only be discharged. "Solid batteries" are preferably "secondary batteries". "Secondary batteries" are not overly rigid in their names, and may also include electrochemical devices such as "power storage devices", for example.

[0116] The solid battery of the present invention includes a positive electrode layer, a negative electrode layer and a solid electrolyte layer, and generally has a stacked structure in which the positive electrode layer and the negative electrode layer are stacked with the solid electrolyte layer interposed therebetween. The positive electrode layer and the negative electrode layer can be stacked in two or more layers respectively as long as they have a solid electrolyte layer between them. The solid electrolyte layer is in contact with the positive electrode layer and the negative electrode layer and is sandwiched by them. It is also possible that the positive electrode layer and the solid electrolyte layer form an integral sintering of a sintered body, and / or the negative electrode layer and the solid electrolyte layer form an integral sintering of a sintered body. The so-called integral sintering of sintered bodies means that two or more adjacent or contacting parts (especially layers) are joined by sintering. Here, the two or more parts (especially layers) are all sintered bodies, and can also be sintered as a whole.

[0117] The above-mentioned solid electrolyte ceramic of the present invention is useful as a solid electrolyte of a solid battery. Therefore, the solid battery of the present invention comprises the above-mentioned solid electrolyte ceramic of the present invention as a solid electrolyte. In detail, the solid electrolyte ceramic of the present invention is contained as a solid electrolyte in at least one layer selected from the group consisting of a positive electrode layer, a negative electrode layer and a solid electrolyte layer. From the viewpoint of more excellent ion conductivity in the solid electrolyte layer and more fully suppressing the increase in electronic conductivity during operation, the solid electrolyte ceramic of the present invention is preferably contained at least in the solid electrolyte layer.

[0118] (Positive electrode layer)

[0119] In the solid battery of the present invention, the positive electrode layer is not particularly limited. For example, the positive electrode layer contains a positive electrode active material and may also contain the solid electrolyte ceramic of the present invention. By containing the solid electrolyte ceramic of the present invention in the positive electrode layer, it is possible to suppress the short circuit of the solid battery. The positive electrode layer may have a sintered body containing positive electrode active material particles. The positive electrode layer may be a layer capable of embedding and de-embedding ions (particularly lithium ions).

[0120] The positive electrode active material is not particularly limited, and the positive electrode active material known in the field of solid batteries can be used. As the positive electrode active material, for example, lithium-containing phosphate compound particles having a NASICON structure, lithium-containing phosphate compound particles having an olivine structure, lithium-containing layered oxide particles, lithium-containing oxide particles having a spinel structure, etc. can be listed. As specific examples of lithium-containing phosphate compounds with a NASICON structure that are preferably used, Li3V2(PO4)3 and the like can be listed. As specific examples of lithium-containing phosphate compounds with an olivine structure that are preferably used, Li3Fe2(PO4)3, LiMnPO4 and the like can be listed. As specific examples of lithium-containing layered oxide particles that are preferably used, LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 As specific examples of lithium-containing oxides with a spinel structure that are preferably used, LiMn2O4, LiNi 0.5 Mn 1.5 O4、Li4Ti5O 12 From the viewpoint of reactivity when co-sintered with the LISICON type solid electrolyte used in the present invention, it is more preferable to use LiCoO2, LiCo 1 / 3 Ni 1 / 3Mn 1 / 3 It should be noted that only one of these positive electrode active material particles may be used, or a plurality of them may be used in combination.

[0121] The positive electrode active material having a NASICON structure in the positive electrode layer means that the positive electrode active material (especially its particles) has a NASICON crystal structure, and in a broad sense, it means a crystal structure that can be identified as a NASICON crystal structure by a person skilled in the art in the field of solid batteries. In a narrow sense, the positive electrode active material having a NASICON structure in the positive electrode layer means that the positive electrode active material (especially its particles) shows one or more main peaks corresponding to the Miller index inherent in the so-called NASICON crystal structure at a specified angle of incidence in X-ray diffraction. As the preferred positive electrode active material having a NASICON structure, the compounds exemplified above can be listed.

[0122] The positive electrode active material having an olivine structure in the positive electrode layer means that the positive electrode active material (especially its particles) has an olivine crystal structure, and in a broad sense, it means a crystal structure that can be identified as an olivine crystal structure by a person skilled in the art in the field of solid batteries. In a narrow sense, the positive electrode active material having an olivine structure in the positive electrode layer means that the positive electrode active material (especially its particles) shows one or more main peaks corresponding to the Miller index inherent in the so-called olivine crystal structure at a specified angle of incidence in X-ray diffraction. As a preferred positive electrode active material having an olivine structure, the compounds exemplified above can be listed.

[0123] The positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (especially its particles) has a spinel crystal structure, and in a broad sense, it means a crystal structure that can be identified as a spinel crystal structure by a person skilled in the art in the field of solid batteries. In a narrow sense, the positive electrode active material in the positive electrode layer has a spinel structure, which means that the positive electrode active material (especially its particles) shows one or more main peaks corresponding to the Miller index inherent in the so-called spinel crystal structure at a specified incident angle in X-ray diffraction. As the preferred positive electrode active material with a spinel structure, the compounds exemplified above can be listed.

[0124] The chemical composition of the positive electrode active material may also be an average chemical composition. The average chemical composition of the positive electrode active material refers to the average value of the chemical composition of the positive electrode active material in the thickness direction of the positive electrode layer. The average chemical composition of the positive electrode active material can be analyzed and measured by breaking the solid battery and using SEM-EDX (energy dispersive X-ray spectroscopy) to perform composition analysis using EDX in the overall field of view of the thickness direction of the positive electrode layer.

[0125] The positive electrode active material can be manufactured, for example, by the following method, or can also be obtained as a commercial product. In the case of manufacturing the positive electrode active material, first, a raw material compound containing a predetermined metal atom is weighed to make the chemical composition into a predetermined chemical composition, and water is added and mixed to obtain a slurry. Next, the slurry is dried, pre-calcined at 700° C. or more and 1000° C. or less for 1 hour or more and 30 hours or less, and then crushed to obtain the positive electrode active material.

[0126] The chemical composition and crystal structure of the positive electrode active material in the positive electrode layer generally change due to element diffusion during sintering. The positive electrode active material may have the above-mentioned chemical composition and crystal structure in the solid battery after sintering together with the negative electrode layer and the solid electrolyte layer.

[0127] The average particle size of the positive electrode active material is not particularly limited, and may be, for example, 0.01 μm or more and 10 μm or less, and preferably 0.05 μm or more and 4 μm or less.

[0128] The average particle size of the positive electrode active material can be determined by, for example, randomly selecting 10 or more and 100 or less particles from a SEM image and simply averaging the particle sizes thereof (arithmetic mean).

[0129] The particle size is the diameter of a spherical particle assuming that the particle is completely spherical. Such a particle size can be obtained, for example, by cutting out a cross section of a solid battery, taking a cross-sectional SEM image using an SEM, and calculating the cross-sectional area S of the particle using image analysis software (e.g., "Azokun" (manufactured by Asahi Kasei Engineering Co., Ltd.)), and then obtaining the particle diameter R by the following formula.

[0130] [Mathematical formula 1]

[0131] R=2×(S / π) 1 / 2

[0132] It should be noted that the average particle size of the positive electrode active material in the positive electrode layer can be automatically measured by determining the composition of the positive electrode active material when measuring the above-mentioned average chemical composition.

[0133] The average particle size of the positive electrode active material in the positive electrode layer generally changes due to sintering in the manufacturing process of the solid battery. The positive electrode active material may have the above average particle size in the solid battery after sintering together with the negative electrode layer and the solid electrolyte layer.

[0134] The volume ratio of the positive electrode active material in the positive electrode layer is not particularly limited, and may be, for example, 30% to 90%, and particularly 40% to 70%.

[0135] The positive electrode layer may contain the solid electrolyte ceramic of the present invention as a solid electrolyte, and / or may contain a solid electrolyte other than the solid electrolyte ceramic of the present invention.

[0136] The positive electrode layer may further contain a sintering aid and / or a conductive material and the like.

[0137] When the positive electrode layer includes the solid electrolyte ceramic of the present invention, the volume ratio of the solid electrolyte ceramic of the present invention can be generally 20% to 60%, and particularly 30% to 45%.

[0138] As the sintering aid in the positive electrode layer, the same compounds as the sintering aid that can be contained in the solid electrolyte ceramic can be used.

[0139] The volume ratio of the sintering aid in the positive electrode layer is not particularly limited, but is, for example, preferably 0.1% to 20%, and more preferably 1% to 10%.

[0140] The conductive material in the positive electrode layer can use conductive materials known in the field of solid batteries. As conductive materials preferably used, for example, metal materials such as Ag (silver), Au (gold), Pd (palladium), Pt (platinum), Cu (copper), Sn (tin), Ni (nickel) and carbon materials such as carbon nanotubes such as acetylene black, Ketjen black, Super P (registered trademark), VGCF (registered trademark) can be listed. There is no particular limitation on the shape of the carbon material, and materials of any shape such as spherical, plate-like, and fibrous can be used.

[0141] The volume ratio of the conductive material in the positive electrode layer is not particularly limited, but is, for example, preferably 10% to 50%, and more preferably 20% to 40%.

[0142] The thickness of the positive electrode layer is usually 0.1 to 30 μm, for example, preferably 1 to 20 μm. The thickness of the positive electrode layer is the average value of thicknesses measured at any 10 locations in the SEM image.

[0143] In the positive electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0144] The porosity of the positive electrode layer was measured from a SEM image after FIB cross-section processing.

[0145] The positive electrode layer is a layer that can be called a “positive electrode active material layer.” The positive electrode layer may have a so-called positive electrode current collector or a positive electrode current collecting layer.

[0146] (Negative electrode layer)

[0147] In the solid battery of the present invention, the negative electrode layer is not particularly limited. For example, the negative electrode layer contains a negative electrode active material and may also contain the solid electrolyte ceramic of the present invention. By containing the solid electrolyte ceramic of the present invention in the negative electrode layer, short circuit of the solid battery can be suppressed. The negative electrode layer may have a sintered body containing negative electrode active material particles. The negative electrode layer may be a layer capable of embedding and de-embedding ions (particularly lithium ions).

[0148] The negative electrode active material is not particularly limited, and negative electrode active materials known in the field of solid batteries can be used. Examples of the negative electrode active material include carbon materials such as graphite, graphite-lithium compounds, lithium metal, lithium alloy particles, phosphate compounds with a NASICON structure, Li-containing oxides with a spinel structure, and β-type lithium-containing oxides. II -Li3VO4 type structure, γ II-Li3VO4 type structure oxides, etc. The negative electrode active material preferably uses lithium metal, which has β II -Li3VO4 type structure, γ II -Li3VO4 type structured Li-containing oxide.

[0149] The oxide in the negative electrode layer has β II -Li3VO4 type structure means that the oxide (especially its particles) has β II -Li3VO4 type crystal structure, in a broad sense, refers to a structure that can be identified as β by those skilled in the art in the field of solid batteries II -Li3VO4 type crystal structure. In a narrow sense, the oxide in the negative electrode layer has β II -Li3VO4 type structure means that the oxide (especially its particles) shows the same as the so-called β-type structure at a specified incident angle in X-ray diffraction. II -Li3VO4 type crystal structure has one or more main peaks corresponding to the Miller index. II -Li3VO4 type structured Li-containing oxides include Li3VO4.

[0150] The oxide in the negative electrode layer has γ II -Li3VO4 type structure means that the oxide (especially its particles) has γ II -Li3VO4 type crystal structure, in a broad sense, refers to a structure that can be identified as γ by those skilled in the art in the field of solid batteries II -Li3VO4 type crystal structure. In a narrow sense, the oxide in the negative electrode layer has γ II -Li3VO4 type structure means that the oxide (especially its particles) shows the same as the so-called γ-ray diffraction at a specified incident angle (x axis) in X-ray diffraction. II -Li3VO4 type crystal structure has one or more main peaks corresponding to the Miller index. II -Li3VO4 type Li-containing oxides, including Li 3.2 V 0.8 Si 0.2 O4.

[0151] The chemical composition of the negative electrode active material may be an average chemical composition. The average chemical composition of the negative electrode active material refers to the average value of the chemical composition of the negative electrode active material in the thickness direction of the negative electrode layer. The average chemical composition of the negative electrode active material can be analyzed and measured by breaking the solid battery and using SEM-EDX (energy dispersive X-ray spectroscopy) to perform composition analysis using EDX in the overall field of view of the thickness direction of the negative electrode layer.

[0152] The negative electrode active material can be produced by, for example, the same method as the positive electrode active material, or can be obtained as a commercial product.

[0153] The chemical composition and crystal structure of the negative electrode active material in the negative electrode layer usually change according to the diffusion of elements during sintering in the manufacturing process of the solid battery. Alternatively, the negative electrode active material has the above-mentioned average chemical composition and crystal structure in the solid battery after sintering together with the positive electrode layer and the solid electrolyte layer.

[0154] The volume ratio of the negative electrode active material in the negative electrode layer is not particularly limited, but is, for example, preferably 50% or more (particularly 50% or more and 99% or less), more preferably 70% or more and 95% or less, and further preferably 80% or more and 90% or less.

[0155] The negative electrode layer may contain the solid electrolyte ceramic of the present invention as a solid electrolyte, and / or may contain a solid electrolyte other than the solid electrolyte ceramic of the present invention.

[0156] The negative electrode layer may further contain a sintering aid and / or a conductive material.

[0157] When the negative electrode layer includes the solid electrolyte ceramic of the present invention, the volume ratio of the solid electrolyte ceramic of the present invention can be generally 20% to 60%, and particularly 30% to 45%.

[0158] As the sintering aid in the negative electrode layer, the same compound as the sintering aid in the positive electrode layer can be used.

[0159] As the conductive material in the negative electrode layer, the same compound as the conductive material in the positive electrode layer can be used.

[0160] The thickness of the negative electrode layer is usually 0.1 to 30 μm, preferably 1 to 20 μm. The thickness of the negative electrode layer is the average value of thicknesses measured at any 10 locations in the SEM image.

[0161] In the negative electrode layer, the porosity is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0162] The porosity of the negative electrode layer was measured by the same method as that of the porosity of the positive electrode layer.

[0163] The negative electrode layer is a layer that can be called a “negative electrode active material layer.” The negative electrode layer may have a so-called negative electrode current collector or a negative electrode current collecting layer.

[0164] (Solid electrolyte layer)

[0165] In the solid battery of the present invention, the solid electrolyte layer preferably includes the above-mentioned solid electrolyte ceramic of the present invention from the viewpoint of achieving more excellent ion conductivity and more fully suppressing an increase in electron conductivity during operation.

[0166] The volume ratio of the solid electrolyte ceramic of the present invention in the solid electrolyte layer is not particularly limited, but is preferably 10% to 100%, more preferably 20% to 100%, and further preferably 30% to 100%, from the viewpoint of achieving better ion conductivity and more adequate suppression of the increase in electronic conductivity during operation.

[0167] In the case where the solid electrolyte layer includes the solid electrolyte ceramic of the present invention, it is sufficient that the solid electrolyte ceramic of the present invention having the chemical composition described above is present in at least the central portion of the thickness direction of the solid electrolyte layer (particularly at least 5 points, preferably at least 8 points, and more preferably 10 points out of any 10 points). This is because the solid electrolyte layer is sandwiched between the positive electrode layer and the negative electrode layer, and due to sintering in the manufacturing process of the solid battery, element diffusion from the positive electrode layer and the negative electrode layer to the solid electrolyte layer and / or element diffusion from the solid electrolyte layer to the positive electrode layer and the negative electrode layer may sometimes occur.

[0168] In the solid electrolyte layer, in addition to the garnet-type solid electrolyte ceramic of the present invention, one or more materials selected from a solid electrolyte composed of at least Li, Zr, and O, a solid electrolyte having a γ-Li3VO4 structure, and an oxide glass ceramic lithium ion conductor can be included. As a solid electrolyte composed of at least Li, Zr, and O, Li2ZrO3 can be cited.

[0169] Examples of the solid electrolyte having a γ-Li 3 VO 4 structure include a solid electrolyte having an average chemical composition represented by the following general formula (III).

[0170] [Chemical formula 4]

[0171] (Li [3-ax+(5-c)(1-y)] A x )(B y D 1-y )O4 (III)

[0172] In formula (III), A is one or more elements selected from the group consisting of Na, K, Mg, Ca, Al, Ga, Zn, Fe, Cr and Co.

[0173] B is one or more elements selected from the group consisting of V and P.

[0174] D is one or more elements selected from the group consisting of Zn, Al, Ga, Si, Ge, Sn, As, Ti, Mo, W, Fe, Cr, and Co.

[0175] x satisfies 0≤x≤1.0, in particular, 0≤x≤0.2.

[0176] y satisfies 0≤y≤1.0, in particular, 0.20≤y≤0.50.

[0177] a is the average valence of A. For example, when A is considered to have n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, the average valence of A is represented by (n1×a+n2×b+n3×c) / (n1+n2+n3).

[0178] c is the average valence of D. For example, when D is considered to be n1 elements X with a valence of a+, n2 elements Y with a valence of b+, and n3 elements Z with a valence of c+, the average valence of D is the same as the average valence of A described above.

[0179] As specific examples of solid electrolytes having a γ-Li3VO4 structure, for example, Li 3.2 (V 0.8 Si 0.2 )O4、Li 3.5 (V 0.5 Ge 0.5 )O4、Li 3.4 (P 0.6 Si 0.4 )O4、Li 3.5 (P 0.5 Ge 0.5 )O4, etc.

[0180] As the oxide glass ceramic-based lithium ion conductor, for example, a phosphate compound (LATP) containing lithium, aluminum, and titanium as constituent elements, and a phosphate compound (LAGP) containing lithium, aluminum, and germanium as constituent elements can be used.

[0181] The solid electrolyte layer may contain, for example, a sintering aid and the like in addition to the solid electrolyte.

[0182] As the sintering aid in the solid electrolyte layer, the same compound as the sintering aid in the positive electrode layer can be used.

[0183] The volume ratio of the sintering aid in the solid electrolyte layer is not particularly limited, but is preferably 0% to 20%, more preferably 1% to 10%, from the viewpoint of achieving better ion conductivity and more adequately suppressing an increase in electronic conductivity during operation.

[0184] The thickness of the solid electrolyte layer is usually 0.1 to 30 μm, and preferably 1 to 20 μm from the viewpoint of better ion conductivity and more sufficient suppression of an increase in electronic conductivity during operation. The thickness of the solid electrolyte layer is the average value of thicknesses measured at any 10 locations in the SEM image.

[0185] The porosity in the solid electrolyte layer is not particularly limited, but is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less from the viewpoint of achieving better ion conductivity and more adequately suppressing an increase in electronic conductivity during operation.

[0186] The porosity of the solid electrolyte layer was measured by the same method as the porosity of the positive electrode layer.

[0187] [Method for manufacturing solid state battery]

[0188] The solid-state battery can be produced, for example, by a so-called green sheet method, a printing method, or a method combining these methods.

[0189] The green sheet method will be described.

[0190] First, a paste is prepared by appropriately mixing a solvent, a binder, etc. with a positive electrode active material. The paste is applied to a sheet and dried to form a first green sheet for constituting a positive electrode layer. The first green sheet may contain a solid electrolyte, a conductive material, and / or a sintering aid, etc.

[0191] The paste is prepared by appropriately mixing a solvent, a binder, etc. with the negative electrode active material. The paste is applied to a sheet and dried to form a second green sheet for constituting the negative electrode layer. The second green sheet may contain a solid electrolyte, a conductive material, and / or a sintering aid, etc.

[0192] A paste is prepared by appropriately mixing a solvent, a binder, etc. with a solid electrolyte. The paste is applied and dried to prepare a third green sheet for constituting a solid electrolyte layer. The third green sheet may contain a sintering aid, etc.

[0193] The solvent used to prepare the first to third green sheets is not particularly limited, and for example, a solvent that can be used to prepare a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid batteries can be used. As the solvent, a solvent that can be used with a binder described later is generally used. Examples of such solvents include alcohols such as 2-propanol.

[0194] The binder used to prepare the first to third green sheets is not particularly limited, and for example, a binder that can be used to prepare a positive electrode layer, a negative electrode layer, or a solid electrolyte layer in the field of solid batteries can be used. Examples of such a binder include butyral resins and acrylic resins.

[0195] Next, the first to third green sheets are appropriately stacked to produce a laminate. The produced laminate may be pressed. A preferred pressing method includes hydrostatic pressing.

[0196] Thereafter, the stacked body is heat treated at, for example, 600 to 800° C., whereby a solid battery can be obtained.

[0197] The printing method will be described.

[0198] The printing method is the same as the green sheet method except for the following matters.

[0199] Ink for each layer is prepared having the same composition as that of the paste for obtaining each layer of the green sheet except that the blending amounts of the solvent and the resin are adjusted to be appropriate for use as ink.

[0200] Printing and lamination are performed using inks for each layer to produce a laminate.

[0201] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples at all and can be implemented with appropriate changes within the scope of the present invention.

[0202] Example

[0203] <Examples 1 to 26 and Comparative Examples 1 to 8>

[0204] [Manufacturing of solid electrolyte ceramics]

[0205] The raw materials used were lithium hydroxide monohydrate LiOH·H2O, lanthanum hydroxide La(OH)3, zirconium oxide ZrO2, tantalum oxide Ta2O5, bismuth oxide Bi2O3, cobalt oxide Co3O4, basic nickel carbonate hydrate NiCO3·2Ni(OH)2·4H2O, manganese carbonate MnCO3, and iron oxide Fe2O3.

[0206] The starting materials were weighed so that the chemical compositions became the chemical compositions shown in Table 1.

[0207] Water was added, the mixture was sealed in a polyethylene can, and the mixture was rotated at 150 rpm for 16 hours on a can stand to mix the raw materials.

[0208] In addition, in consideration of Li deficiency during heat treatment, lithium hydroxide monohydrate LiOH·H 2 O was added in an excess amount of 3 wt % as a Li source relative to the target composition.

[0209] The obtained slurry was evaporated and dried, and then pre-calcined in O 2 at 900° C. for 5 hours to obtain the target phase.

[0210] The calcined powder was added with a mixed solvent of toluene and acetone, and pulverized for 12 hours using a planetary ball mill. The pulverized powder was measured by ICP, and it was confirmed that there was no composition deviation. The average particle size of the pulverized powder at this time was 150 nm.

[0211] [Manufacturing of solid electrolyte single sheet]

[0212] As a sample for evaluating the solid electrolyte ceramic, a solid electrolyte single plate was produced by the following method.

[0213] The obtained solid electrolyte powder, butyral resin, and alcohol were fully mixed at a weight ratio of 200:15:140, and then the alcohol was removed on a hot plate at 80° C. to obtain a powder coated with the butyral resin as a binder.

[0214] Next, the coated powder was compressed at 90 MPa using a tablet molding machine to form a tablet.

[0215] The tablets were fully covered with the mother powder, degreased at 500°C in an oxygen atmosphere to remove the butyral resin, then heat treated at about 1200°C for 3 hours in an oxygen atmosphere and cooled to room temperature to obtain a sintered body of the solid electrolyte.

[0216] The surface of the obtained sintered body was ground to obtain a garnet solid electrolyte single plate.

[0217] [Crystal structure of solid electrolyte single plate]

[0218] In all the examples and comparative examples, it was confirmed that an X-ray diffraction pattern attributable to a garnet-type crystal structure was obtained by X-ray diffraction of the solid electrolyte single plate (ICDD Card No. 00-045-0109).

[0219] [Chemical composition of solid electrolyte single plate]

[0220] The solid electrolyte single plate is subjected to ICP analysis to obtain the average chemical composition of the solid electrolyte single plate. The contents of Co, Mn, Ni and Fe in the average chemical composition of the entire solid electrolyte single plate are calculated by dividing the number of 8 coordination sites of the garnet crystal structure (e.g., La and B in the above general formula (II) by 100). 1 It should be noted that O (oxygen) in the chemical composition is a value calculated based on the molar ratio and valence of the elements contained in A, B, and D in the general formula (I) so that charge neutrality is established.

[0221] [Electronic conductivity measurement]

[0222] An Au electrode was sputtered on one side of the obtained single plate as a working electrode. Li metal with the same area as the Au electrode was pasted on the other side. Finally, the battery cell was sealed in a 2035-size coin battery as an evaluation battery cell. All the above operations were carried out in a dry room with a dew point below -40°C.

[0223] A voltage of 2 V relative to Li was applied to the working electrode at room temperature, and the transition current was observed. The current flowing after the voltage was applied for 10 hours was read as the leakage current. The electronic conductivity was calculated using the following formula based on the leakage current.

[0224] Electronic conductivity = (I / V) × (L / A)

[0225] (I: leakage current, V: applied voltage, L: solid electrolyte single plate thickness, A: electrode area)

[0226] ◎: Electronic conductivity <1.0×10 -8 S / cm(excellent);

[0227] ○:1.0×10 -8 S / cm≤Electronic conductivity<5.0×10 -8 S / cm (good);

[0228] △: 5.0×10 -8 S / cm≤Electronic conductivity<1.0×10 -7 S / cm (ok) (no problem in practice);

[0229] ×: 1.0×10 -7 S / cm ≤ electronic conductivity (not possible) (problematic in practice).

[0230] [Ionic conductivity measurement]

[0231] After forming a gold (Au) layer as a collector layer by sputtering on both sides of the solid electrolyte single plate, it was sandwiched and fixed with a SUS collector. The sintered sheets of each solid electrolyte were subjected to AC impedance measurement in the range of 10 MHz to 0.1 Hz (±50 mV) at room temperature (25°C) to evaluate the ion conductivity.

[0232] ◎:1.3×10 -3 S / cm≤ ion conductivity (excellent);

[0233] ○:1.0×10 -3 S / cm≤Ionic conductivity<1.3×10 -3 S / cm (good);

[0234] △: 4.0×10 -4 S / cm≤Ionic conductivity<1.0×10-3 S / cm (ok) (no problem in practice);

[0235] ×: ion conductivity <4.0×10 -4 S / cm (not possible) (problematic in practice).

[0236] [Comprehensive judgment]

[0237] All evaluation results of electronic conductivity and ionic conductivity were comprehensively judged.

[0238] ◎: All evaluation results of the electron conductivity and the ion conductivity were ◎.

[0239] ○: The lowest evaluation result among all the evaluation results of electron conductivity and ion conductivity is ○.

[0240] △: The lowest evaluation result among all the evaluation results of electron conductivity and ion conductivity is △.

[0241] ×: The lowest evaluation result among all the evaluation results of electron conductivity and ion conductivity is ×.

[0242] [Table 1]

[0243]

[0244] [Table 2]

[0245]

[0246] From the comparison between Comparative Examples 1 and 2 and Examples 1 to 4, it can be seen that when the content of the second transition metal element (particularly Ta) is less than 12.0 mol %, the ion conductivity decreases.

[0247] From the comparison of Examples 1 to 4 with Comparative Example 3, it can be seen that when the content of the second transition metal element (especially Ta) is within the range of 12 mol% or more and less than 20.0 mol%, and when the content of the first transition metal element (especially Co) is greater than 4.00 mol%, the electronic conductivity becomes higher and the risk of short circuit increases.

[0248] From the comparison of Examples 5 to 10 with Comparative Examples 4 and 5, it can be seen that when the content of the second transition metal element (especially Ta) is within the range of 20.0 mol% or more and less than 33.0 mol%, and when the content of the first transition metal element (especially Co) is greater than 6.00 mol%, the electronic conductivity becomes higher and the risk of short circuit increases.

[0249] From the comparison of Examples 11 to 22 with Comparative Examples 6 to 8, it can be seen that when the content of the second transition metal element (especially Ta) is within the range of 33.0 mol% to 65.5 mol%, and when the content of the first transition metal element (especially Co) is greater than 8.00 mol%, the electronic conductivity becomes higher and the risk of short circuit increases.

[0250] Industrial Applicability

[0251] The solid battery including the solid electrolyte ceramic of the present invention can be applied to various fields where batteries or power storage are assumed to be used. Although it is only an example, the solid battery according to one embodiment of the present invention can be applied to the field of electronic devices. The solid battery involved in one embodiment of the present invention can also be applied to the following fields: electrical / information / communication fields using mobile devices, etc. (for example, electrical / electronic equipment fields or mobile equipment fields including small electronic devices such as mobile phones, smart phones, smart watches, laptops, digital cameras, activity meters, ARM computers, electronic paper, wearable devices, RFID tags, card-type electronic currency, smart watches, etc.); household / small industrial uses (for example, the fields of power tools, golf carts, household / nursing / industrial robots); large industrial uses (for example, the fields of forklifts, elevators, and port cranes); transportation system fields (for example, hybrid vehicles, electric vehicles, buses, trams, electric-assisted bicycles, electric motorcycles, etc.); power system uses (for example, various power generation, load regulators, smart grids, general household-installed power storage systems, etc.); medical uses (medical equipment fields such as headphones and hearing aids); pharmaceutical uses (dose management systems, etc.); and IoT fields; space / deep sea uses (for example, space probes, submersible survey ships, etc.), etc.

Claims

1. A solid electrolyte ceramic having a garnet-type crystal structure, contains at least lithium Li, lanthanum La, bismuth Bi and oxygen O, and contains one or more transition metal elements selected from the group consisting of cobalt Co, nickel Ni, manganese Mn and iron Fe, Having a chemical composition represented by the following general formula (I), A α B β D γ O ω (I) In formula (I), A is one or more elements selected from the group consisting of lithium Li, gallium Ga, aluminum Al, magnesium Mg, zinc Zn and scandium Sc, and contains at least lithium Li; B is one or more elements selected from the group consisting of La, calcium, strontium, barium, and lanthanide elements, and contains at least lanthanum, La; D is one or more elements selected from the group consisting of transition elements capable of forming hexacoordinates with oxygen and typical elements belonging to Groups 12 to 15, and contains at least bismuth Bi; α satisfies 5.0≤α≤8.0; β satisfies 2.5≤β≤3.5; γ satisfies 1.5≤γ≤2.5; ω satisfies 11≤ω≤13, When the content of D is X when the content of B is 100 mol %, and the total content of the transition metal elements is Y, any one of the following relationship equations (1) to (3) is satisfied: (1) 0.01≤Y≤4.00 in the range of 12.0≤X<20.0; (2) 0.01≤Y≤6.00 in the range of 20.0≤X<33.0; (3) 0.01≤Y≤8.00 in the range of 33.0≤X≤65.5, X and Y are expressed in mol%.

2. The solid electrolyte ceramic according to claim 1, wherein The transition metal element includes Co.

3. The solid electrolyte ceramic according to claim 1 or 2, wherein: The D contains one or more additional transition metal elements selected from the group consisting of tantalum Ta and niobium Nb.

4. The solid electrolyte ceramic according to claim 3, wherein The additional transition metal element contains Ta.

5. The solid electrolyte ceramic according to claim 1 or 2, wherein: The solid electrolyte ceramic satisfies the relational expression (1) or (2).

6. The solid electrolyte ceramic according to claim 1 or 2, wherein: The solid electrolyte ceramic satisfies the relational expression (1).

7. The solid electrolyte ceramic according to claim 1 or 2, wherein: The D contains tantalum Ta, The content X of D is the content of tantalum Ta.

8. A solid battery, A solid electrolyte ceramic comprising the solid electrolyte ceramic according to any one of claims 1 to 7.

9. The solid battery according to claim 8, wherein: The solid battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer stacked between the positive electrode layer and the negative electrode layer. The positive electrode layer and the negative electrode layer are layers capable of inserting and releasing lithium ions.

10. The solid battery according to claim 9, wherein: The solid electrolyte layer, the positive electrode layer, and the negative electrode layer are sintered integrally with each other to form a sintered body.

11. The solid battery according to any one of claims 8 to 10, wherein The solid electrolyte ceramic is contained in a solid electrolyte layer of the solid battery.

Citation Information

Patent Citations

  • Solid electrolyte ceramics material

    JP2015050071A

  • Stabilization coatings for solid state batteries

    CN110036504A